Molecular analysis of T cell receptor beta variability in a patient with orofacial granulomatosis. Issue 5 (May 1997) - Lim, S H; Stephens, P; Cao, Q X; Coleman, S; Thomas, D W
Abstract : BACKGROUND: Orofacial granulomatosis (OFG) is a rare chronic inflammatory disorder of unknown causation and is characterised histologically by non-caseating granulomas and aggregates of small lymphocytes. The molecular nature of these T cells is, however, unclear. AIMS: To determine the T cell receptor (TCR) V beta gene usage of the T cell infiltrate associated with the primary lesions in a patient with OFG. METHODS: A molecular method involving reverse transcriptase (RT)-polymerase chain reaction (PCR), DNA cloning, single strand conformation polymorphism (SSCP), length analysis, and nucleotide sequencing was used. RESULTS: Compared with peripheral blood lymphocytes from the same patient, notably restricted TCRV beta gene usage was observed in the T cell infiltrate. Only three of the 24 major TCRV beta gene families were represented in the repertoire. There was preferential usage of the V beta 6 gene. In addition, more than 20% of the V beta 6 TCR transcripts exhibited an identical unique V-D-J junctional sequence, suggesting a local antigen driven V beta 6 T cell clonal expansion in vivo, a phenomenon not observed in normal oral mucosa. CONCLUSIONS: The TCRV beta repertoire of T cells associated with OFG is restricted. It is also associated with a local T cell clonal expansion. The results, therefore, provide a new perspective on the immunopathology of OFG.